Experiencing Students' Difficulties in Learning Abstract Algebra - Subedi, Abatar (Tribhuvan University Journal, 2020)
This paper aims to reveal the difficulties as experienced by graduate students while learning abstract algebra at master's degree in mathematics education in the first month of their enrollment. For, I adopted a case study of five students, interviewed them with the help of interview guidelines and observed their behaviors in the classroom, and triangulated this information with researcher’s experiences to explore the difficulties in learning abstract algebra. I used inductive method to analyze the information and concluded that graduate students have experienced several difficulties in learning abstract algebra including the difficulties in conceptualizing algebraic facts, constructing examples and non-examples; and proving theorems. Finally, the study suggests that graduate teaching need to focus on conceptual and procedural understanding of students, and emphasizing to construct examples and non-example as much as possible to improve students’ learning.